Implementation Of CMS-Based E-Commerce Using The Business Model Canvas Method at Noru Label - Adeline, Bianca Vania; Aryasanti, Agnes; Diana, Anita; Anif, Mohammad (Universitas Budi Luhur, 2024)
Currently, product marketing in business can be easily conducted thanks to the rapid advancement of information technology. Many stores engage in online buying and selling activities, commonly referred to as E-Commerce. Noru Label is a bag store that sells tote bags and laptop bags, primarily relying on social media and marketplaces as sales platforms. However, in conducting business through social media and marketplaces, Noru Label faces several issues. Customers often struggle to obtain product information such as stock availability, prices, and product descriptions on social media, requiring them to inquire first and wait for the admin’s response, which can sometimes take a long time. Another issue is the high cancellation rate on Shopee, which stands at 34%, causing losses for Noru Label as products are already packaged and ready for shipment. Additionally, there are instances of product returns due to customers ordering the wrong items or receiving damaged goods during shipping, despite Noru Label always ensuring that products are thoroughly checked and free of defects before dispatch. Moreover, when searched on Google, Noru Label’s products have yet to appear on the first page of results. The aim of this study is to design an E-Commerce website using a Content Management System (CMS) to facilitate customers in ordering and transaction processes, implement E-Commerce at Noru Label to boost sales and marketing without causing losses to the seller, and utilize Search Engine Optimization (SEO) to enhance promotion and reach a wider market segment. The results of this study indicate that the E-Commerce website allows customers to explore products with more comprehensive information and clearer descriptions. Additionally, with SEO as a supplementary promotional strategy, Noru Label can market its products to a broader audience, and the high cancellation rate can be reduced due to the different features available on the E-Commerce website.